ENTREPRENEURIAL E-COMMERCE MARKETING TO IMPROVE THE PERFORMANCE OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) IN BANDAR LAMPUNG CITY - Komang Yunita Shakpuytri; Ni Putu Widhia Rahayu (Transpublika Publisher, 2024)
In Bandar Lampung, approximately 18% of MSMEs have not embraced e-commerce, despite its growing popularity and convenience. Limited access to technology and the internet, lack of digital literacy, concerns about security and trust, and traditional business practices are all factors contributing to this low adoption rate. This research aims to empirically investigate how digital marketing affects intellectual capital, perceived quality, and overall performance of MSMEs. Additionally, it explores the impact of MSMEs' intellectual capital and perceived quality on their performance. Employing a quantitative approach with descriptive analysis, this study targets MSME actors in Bandar Lampung. The sampling strategy involves multi-stage cluster purposive sampling, selecting 366 respondents for data collection through an online questionnaire using Likert scales. The analysis is conducted using Smart PLS, and the results reveal that digital marketing significantly and positively influences intellectual capital, perceived quality, and overall performance of MSMEs. Furthermore, both intellectual capital and quality perception show a positive and significant influence on MSME performance.